Antiretroviral adherence among rural compared to urban veterans with HIV infection in the United States. - Ohl, Michael E; Perencevich, Eli; McInnes, D Keith; Kim, Nancy; Rimland, David; Akgun, Kathleen; Fiellin, David A; Skanderson, Melissa; Wang, Karen; Justice, Amy (AIDS and behavior, 2013)
Rural-dwelling persons with HIV infection face barriers to maintaining high levels of antiretroviral adherence. We compared adherence among 1,782 rural and 18,519 urban veterans initiating antiretroviral therapy in the Veterans Affairs (VA) healthcare system in the United States between 1998 and 2007. Residence was determined using rural urban commuting area codes and adherence using pharmacy-based refill measures. The median proportion of days covered (PDC) by combination antiretroviral therapy in the first year of treatment ranged from 0.72 among urban residents to 0.79 among rural-small town/remote residents (p < 0.0001). In multivariable logistic regression, predictors of high adherence (PDC greater than 0.90) were residence in a rural-small town/remote setting (odds ratio 1.24, 95 % CI 1.09-1.56, relative to urban), increasing age, white race, absence of an alcohol or substance use disorder, and absence of hepatitis C infection. Results may differ outside VA healthcare, where there may be fewer resources to support adherence among rural-dwelling persons with HIV.
Keywords: Adult; Anti-Retroviral Agents; Confidence Intervals; Female; Follow-Up Studies; HIV Infections; Humans; Logistic Models; Male; Medication Adherence; Middle Aged; Odds Ratio; Residence Characteristics; Retrospective Studies; Rural Population; Socioeconomic Factors; United States; United States Department of Veterans Affairs; Urban Population; Veterans